ADAMTS‐13 and bleeding phenotype in von Willebrand disease. Issue 8 (31st October 2020) - Boender, Johan; Nederlof, Angelique; Meijer, Karina; Mauser‐Bunschoten, Evelien P.; Cnossen, Marjon H.; Fijnvandraat, Karin; van der Bom, Johanna G.; de Meris, Joke; Laros‐van Gorkom, Britta A. P.; van Galen, Karin P. M.; Eikenboom, Jeroen; de Maat, Moniek P. M; et al.
Abstract: Background: The bleeding phenotype of von Willebrand disease (VWD) varies highly between patients and can only partly be explained by von Willebrand factor (VWF) parameters. By cleaving large VWF multimers into smaller, less active multimers, ADAMTS‐13 is an important regulator of VWF activity. However, it is unknown what the role of ADAMTS‐13 is in individuals with VWD. Objectives: We therefore studied how ADAMTS‐13 activity is associated with the laboratory and bleeding phenotype in individuals with VWD. Methods: We measured ADAMTS‐13 activity using the fluorescence resonance energy transfer substrate VWF 73 assay in 638 individuals with VWD in the nationwide cross‐sectional Willebrand in the Netherlands study and in 36 healthy controls. The bleeding phenotype was assessed using the Tosetto bleeding score. Results: ADAMTS‐13 activity was similar in individuals with VWD (109% ± 20.6%) and controls (110% ± 19.7%). ADAMTS‐13 activity was higher in individuals with VWD with type 3 than those with type 1 (mean difference, 11.8%; 95% confidence interval [CI], 2.9%‐20.8%) or type 2 (mean difference, 16.1%; 95% CI, 7.1%‐25.1%). ADAMTS‐13 activity was not associated with the Tosetto bleeding score (0.1 Tosetto bleeding score increase per 10% ADAMTS‐13 increase, 95% CI, −0.2 to 0.3). Furthermore, ADAMTS‐13 activity did not differ between individuals with and without a bleeding event during the year preceding blood sampling (mean difference, 1.4%; 95% CI, −2.1% to 4.9%). Conclusion: ADAMTS‐13 activity was highest in individuals with type 3 VWD, but it had only minor associations with VWF parameters. ADAMTS‐13 activity does not influence the bleeding phenotype in individuals with VWD.